Analysis of protein content of two kelps, Ecklonia maxima and Laminaria pallida for feed in abalone aquaculture - Forbes, Cherie Janine (Department of Biological Sciences, 2017)
Kelp is widely used as feed in the abalone aquaculture industry in South Africa, and farmers have reported different feed quality between the two dominant kelp species occurring along the west and southwest coasts with Ecklonia maxima reported as having a better Food Conversion Ratio (FCR) than Laminaria pallida. Total protein content and other nutritional components (Carbon, Nitrogen and moisture content) of two kelp species, E. maxima and L. pallida were investigated. The kelps were collected from Kommetjie (borderline of west and southwest coasts). Seasonal total protein content of E.maxima from a commercially-harvested kelp bed in Jacobsbaai (west coast) was compared with crude protein levels (measured as %N x 6.25). Total protein was extracted and quantified using the Bradford method. No significant difference in carbon content was found between seasons for E. maxima but there was a significant difference in average carbon content between E. maxima (30.79 %) and L. pallida (27.79 %). No seasonal pattern was observed in the nitrogen content, and hence crude protein content, of E. maxima (seasonal crude protein averaged 7.8% of dry weight) and there was no significant difference found between E. maxima and L. pallida (crude protein averaged 9. 05% of dry weight). There was no significant seasonal difference in total protein (averaged 0.99% of dry weight) and no significance found between species. The reported better FCR in abalone feed comprised of E. maxima rather than L.pallida, if correct, is likely to be related to higher carbohydrate content (measured here as carbon) and not to higher protein content. E. maxima differs from L. pallida with regards to carbon storage, but not protein content